Peningkatan Kemampuan Siswa Dalam Pemasangan Komponen Dan Sirkit Motor Kontrol Non Programmable Logic Control (NON PLC) Pada Siswa Kelas XI TITL2 SMK Negeri 1 Merdeka Melalui Penerapan Project Based Learning Di Semester 1 Tahun Pelajaran 2020/2021 - Tonny Hutagalung (Pusdikra Publishing, 2022)
The results of the research and discussion, it was concluded that the application of Project Based Learning used in Electric Motor Installation lessons material for Installation of Non-Programmable Logic Control (Non PLC) Motor Control Components and Circuits can improve Students' Ability in Installing Non-Programmable Logic Control Motor Control Components and Circuits ( Non PLC) students of class XI TITL2 SMK Negeri 1 Merdeka proven on Pre-cycle the average value of Students' Ability in Installing Components and Motor Control Circuits Non Programmable Logic Control (Non PLC) students 53.87 with 12 out of 31 students who pass increased in cycle I to 66.13 with 15 students who completed then in cycle II it increased again, namely 85.16 with 28 students who completed out of 31 students in class XI TITL2 SMK Negeri 1 Merdeka. Meanwhile, the percentage of KKM achievement also increased from Pra-cycle 38.71%, increased in cycle I to 48.39% and increased again to 90.32% in cycle II. These results have exceeded the KKM expected in this study, namely ?70, thus this study is considered to have succeeded in achieving the objectives of this study.